Root canal morphology of mandibular first molars: Comparison of the diagnostic accuracy of cone-beam computed tomography and the sectioning technique - Mohammad Yazdizadeh; Parniyan Alavinezhad; Abtin Sadrishahrezaei; Sanaz Sharifishoshtari (Wolters Kluwer Medknow Publications, 2023)
Background: A successful endodontic treatment requires a comprehensive knowledge of the root canal morphology. This study compared the diagnostic accuracy of cone-beam computed tomography (CBCT) and the sectioning technique for the assessment of mandibular first molar (MFM) root canal morphology. Materials and Methods: In this in vitro, experimental study, 48 eligible MFMs were mounted in 12 blocks (groups of 4) made of acrylic resin and sheep bone powder and underwent CBCT. Next, the teeth were mounted in transparent self-cure acrylic blocks, and their roots were sectioned at three points with 3 mm intervals. Images underwent multiplanar reconstruction in NNT Viewer software and were analyzed by one radiologist with the cooperation of an endodontist. The sections were also evaluated by an endodontist under a stereomicroscope (gold standard). The frequency and percentage of single-canal, and two-canal roots were determined by each technique. The agreement between CBCT and the Gold standard was analyzed by calculating the kappa coefficient (P < 0.05). Results: The diagnostic accuracy of CBCT for the assessment of the MFM root canal morphology was 80% on the mesial surface, 99% in the distal surface, and 96% in total. In the mesial surface, 94.2% of two-canal roots and 66.7% of single-canal roots were correctly detected by CBCT. These values were 100% and 97.4% in the distal surface, and 95.2% and 95.8% in total, respectively. A significant agreement was noted between CBCT and the Gold standard with κ =0.412 for the mesial, 0.939 for the distal, and 0.907 for the total surfaces (P < 0.001). Conclusion: CBCT can be reliably used for the assessment of the complex root canal morphology of MFMs when other modalities fall short.